More than 10 years of industry 4.0 in the Netherlands: an opinion on promises, achievements, and emerging challenges - A. Martinetti; K. Nizamis; P. Chemweno; C. Goulas; L.A.M. van Dongen; I. Gibson; S. Thiede; E. Lutters; T. Vaneker; G. M. Bonnema (International Journal of Sustainable Engineering)
The concept of Industry 4.0, as a means to move forward in the industrial ecosystem, has reached an important turning point. Where do we stand now in terms of industrial innovation and transition? This opinion paper provides an overview of the situation in the Netherlands, a reflection on what has been achieved by the Industry 4.0 paradigm, and the necessary way forward to solidify its implementation. Tentative results reveal that the pervasiveness of Industry 4.0 applications is sector-specific. This work provides industrial stakeholders and academics with useful suggestions and a possible path to move towards better integration of Industry 4.0 in company reality. In this opinion paper, we employ a mixed methods research methodology to argue that, based on our findings on industrial adaptation in The Netherlands, Industry 4.0 is the outcome of an evolutionary process and not of a revolution, as it is often claimed.